(untitled) (Mustansiria Dental Journal, 2018)
Anatomy and growth of the cervical vertebrae attracted attention, since a number of authors proposed developmental association between different variables indicative of cervical vertebral anatomy and dentofacial build. This study aims to verify the morphology of the atlas vertebra and its relationship with the morphology of the mandible. A total of (41) true lateral radiographs (22 females and 19 males) for subjects with an age range of 18-26 years old were selected and subjected to cephalometric analysis. The results show that all the measurements are higher in males than in females except that for the gonial angle and there are a statistically significant differences in mean values of atlas ventral height, ramus length, ramus width and body length among the three groups of atlas a-p length (short, average, long) which increased as the atlas a-p length increased. While among the three groups of atlas dorsal height (low, average, high), there are statistically significant differences in the mean values of gonial angle which decreased as the atlas dorsal arch height increased. It is concluded that there is an association between atlas morphology and mandibular growth.